Influence of Street Canyon's Microclimate on the Energy Demand for Space Cooling and Heating of Buildings. (November 2016) - Vallati, A.; Grignaffini, S.; Romagna, M.; Mauri, L.; Colucci, C.
Abstract: Since an important part of the world's energy is used for space cooling and heating of buildings, its minimization has great energy saving potential. Heat exchange between buildings and surrounding environment is due to convective and radiative heat flows. In this study a detailed building energy simulation (BES) has been carried out in order to analyze the effect of neighbouring buildings on these heat flows and in order to quantify mutual influence on the space cooling and heating demand of buildings. BESs were conducted for a stand-alone building and for a building situated in a typical street canyon. This study demonstrates the importance of considering the urban microclimate conditions for the prediction of the energy demand of buildings. With the implemented model most of the thermal effects of the urban microclimate can be modeled and quantified on a street canyon scale. Due to multiple reflections higher values of solar and thermal radiation are absorbed at the façades of buildings in street canyons than those that occur at stand-alone buildings façades. These effects cause higher surface temperatures in street canyons which means higher space cooling and lower space heating demands. Other reasons that cause this phenomenon are the lower convective heat transfer coefficients in street canyons that results in a reduction of the heat removal from street canyons and contribute to plump the urban heat island effect.